Information Security popularization initiatives: A survey - Rocha, Helter C.; Klein, Erick S.; Rimes, Leonardo S.; Lazarin, Nilson M. (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2022: Companion Proceedings of the 18th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi_estendido.2022.222787, 2022)
This article contains an analysis of the level of popularization of initiatives for digital education and information security on the Internet. They are CERT.BR, ICANN, and SEGURANET, through the study of platforms and means of dissemination of these initiatives, to compare the initiatives. By surveying the traffic of their respective websites, social networks, and services developed. The mission of each initiative and how they are financed is also addressed.